ON THE EXISTENCE OF SOLUTIONS FOR A HADAMARD-TYPE FRACTIONAL INTEGRO-DIFFERENTIAL INCLUSION - Cernea, A. (Journal of Nonlinear Analysis and Optimization: Theory & Applications (JNAO), 2016)
We study a class of fractional integro-differential inclusions with nonlocal fractional integral boundary conditions and we establish a Filippov type existence result in the case of nonconvex set-valued maps.